Host‐specific salivary elicitor(s) of European corn borer induce defenses in tomato and maize. Issue 1 (29th April 2013) - Louis, Joe; Peiffer, Michelle; Ray, Swayamjit; Luthe, Dawn S.; Felton, Gary W.
Summary: Plants turn on induced defenses upon insect herbivory. In the current study, we evaluated the role of European corn borer (ECB) elicitors (molecules secreted by herbivores) that either induce/suppress defenses in Solanum lycopersicum (tomato) and Zea mays (maize), two very important crop plants that are grown for food and/or fuel throughout the world. We used a combination of molecular, biochemical, confocal and scanning electron microscopy, caterpillar spinneret ablation/cauterization, and conventional insect bioassay methods to determine the role of ECB elicitors in modulating defenses in both tomato and maize crop plants. Our results clearly demonstrate that the components present in the ECB saliva induce defense‐related proteinase inhibitors in both tomato ( PIN2 ) and maize ( MPI ). Presence of glucose oxidase in the ECB saliva induced defenses in tomato, but not in maize. However, ECB saliva induced genes present in the jasmonic acid biosynthesis pathway in both tomato and maize. Although ECB saliva can induce defenses in both tomato and maize, our results suggest that host‐specific salivary components are responsible for inducing host plant defenses. Proteomic analysis of ECB salivary elicitors and plant receptors/signaling mechanisms involved in recognizing different ECB elicitors remains to be determined.